The occupation of Japan : - Fearey, Robert A. (Macmillan, 1950)
This book, which was in proof before the June 25th invasion of South Korea had occurred, takes on a new significance because of that attack. The problems of American policy in Japan and of Japan's present and future role in the political, economic and strategic alignments of Asian countries are now seen to be of far greater practical significance than they were before American military unpreparedness in East Asia was so tragically revealed in Korea.